Surviving capital suppression: Strategies for SMEs in China - Nuo Zhou (2023)
In China, SMEs faced a variety of challenges, in particular capital encirclement and oppression. The research aims to identify strategies that SMEs can adopt to overcome these barriers to growth and innovation across various aspects of SMEs, including supply chain risk, sustainability, circular business models, and inclusive digital finance. The study will use a qualitative research methodology based on in-depth interviews to collect data from 20 Chinese SMEs facing capital siege to explore the problem, its impact, trends, causes, best solutions, and the benefits of solving the problem. The study recommends that Chinese SMEs invest in building and nurturing social networks to support their innovation and globalization goals. Policymakers are advised to take steps to increase SMEs' access to inclusive digital finance, as this can improve their ability to innovate and expand. The findings of the study emphasize the importance of sustained digital transformation to improve the efficiency of SMEs. Based on a qualitative research design and thematic analysis of the literature review, this study provides a practical approach for SMEs to escape from capital encirclement and repression.